Do’a dalam Tradisi Agama-Agama - Kuswandi, Yudi (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2018)
This article describes that prayer is the peak expression in religion. The prayer is a primordial form that characterizes spiritualism. Spirituality is indeed a thing that cannot be separated from humans. Berdo'a is a spiritual communication between the servant's self and his Lord. Prayer is the privilege of speaking, greeting and pleading to the Almighty. Munajat is a privilege that belongs to humans, for that prayer should be well studied and applied to the side of human life, both Muslims, Christians, Jews, Buddhists, Hindus and other religions. With sincerity in studying prayer, it is hoped that people can communicate and relate to God correctly. So that it can solve all the problems that are being and will be faced.